Project – Based Learning as a Strategy to Improve Structure and Language Features in Explanatory Text - Lailatul Qadriyah Umarella; S Binnendyk; Rosina F. J. Lekawael (ITScience (Information Technology and Science), 2026)
Mastery of explanatory text writing requires students to organize ideas logically and to apply appropriate language features that reflect causal and sequential relationships. Nevertheless, many EFL students encounter difficulties in structuring explanatory texts and maintaining linguistic accuracy. Although Project-Based Learning (PjBL) has been widely reported to improve general writing performance, limited studies have specifically examined its impact on the generic structure and language features of explanatory texts at the senior high school level. This study aims to investigate the effectiveness of PjBL in improving students’ mastery of explanatory text structure and language features. A pre-experimental one-group pretest–posttest design was employed involving 35 eleventh-grade students of SMA Negeri 5 Maluku Tengah. Data were collected through writing tests assessed using an analytic rubric focusing on general statements, explanation sequences, concluding statements, and relevant language features. The data were analyzed using descriptive statistics and a paired-sample t-test at a significance level of 0.05. The findings revealed a significant improvement in students’ writing performance, indicated by an increase in the mean score from 64.31 to 73.63 and a rise in mastery achievement from 17% to 80%. The statistical result (p < 0.05) confirms that PjBL significantly enhances students’ ability to organize explanatory text structure and apply appropriate linguistic features. These findings suggest that PjBL is an effective instructional strategy for strengthening genre-based writing competence in EFL senior high school contexts.